Artificial Muscles: Recent Progress in Artificial Muscles for Interactive Soft Robotics (Adv. Mater. 19/2021). Issue 19 (11th May 2021) - Wang, Jiangxin; Gao, Dace; Lee, Pooi See
Abstract : Artificial muscles are developed to achieve dexterous shape morphing, manipulation, and locomotion in soft robotics. In article number 2003088, Jiangxin Wang, Pooi See Lee, and Dace Gao provide a succinct and critical summary of the material strategies and actuation mechanisms contributing to recent advancements in this research area, and also discuss the prospects in integrating artificial muscles with multimodal soft sensing and responsive devices to enable smart and interactive soft robotic systems.